Proteomics in Pathology. Issue 2 (24th January 2018) - Longuespée, Rémi; Casadonte, Rita; Schwamborn, Kristina; Reuss, David; Kazdal, Daniel; Kriegsmann, Katharina; von Deimling, Andreas; Weichert, Wilko; Schirmacher, Peter; Kriegsmann, Jörg; Kriegsmann, Mark
Abstract: Proteomic approaches are of growing importance in the biologist's toolbox. It greatly benefited from past and recent advances in sampling, chemical processing, mass spectrometry (MS) instrumentation, and data processing. MS‐based analysis of proteins is now in the process of being translated in pathology for objective diagnoses. In this viewpoint, we present the workflows that we think are the most promising for applications in pathology. We also comment what we think are prerequisites for a successful translational implementation.